Acute cholecystitis in a post-operated patient of subtotal laparoscopic cholecystectomy: case report - R. Muñoz, Braulio; D. Gutiérrez, Carlos; Pereyra de la Cruz , Hugo E. (International Surgery Journal, 2024)
Acute cholecystitis in the remnant of the gallbladder’s wall is a rarely reported condition, which occurs in the 1.6% of all subtotal cholecystectomies, due to gallstones occluding the cystic duct. Symptomatology is variable and may be confused with other pathologies that begin after gallbladder surgery. In the following case we present an elderly woman who arrived at the emergency department with classic acute cholecystitis symptoms, she underwent a fenestrated subtotal laparoscopic cholecystectomy due to severe inflammation in the area of dissection. Ten months later, she returned with a similar clinical picture, ultrasound was performed showing a small-sized gallbladder with gallstones inside. Open cholecystectomy was performed due to adherences, the gallbladder was opened to extract the gallstones, likewise, dissection of the Hartmann’s pouch until identified cystic duct, which was ligated along with the cystic artery. The patient’s postoperative course was favorable, symptomatology disappeared after one day of the surgery. This is an interesting subject which needs to be widely known, therefore, we present the following case report.